Effect of fruit thinners at different volumes on ’Gala’ apple tree - Camilo, Anísio Pedro; Palladini, Luiz Antonio (Pesquisa Agropecuaria Brasileira, 2000)
The aim of this trial was to compare the thinning efficiency of chemicals sprayed at different volumes, in apple (Malus domestica Borkh), cultivar Gala. Naphthaleneacetic acid (NAA) (15 g/ha of a.i.) and carbaryl (1-naphthyl-N-methylcarbamate) (1,000 g/ha of a.i.) were used in spray solutions at 16, 300, 430, 950, 1,300 and 1,900 L/ha maintaining the dose of each product per hectare. NAA was sprayed at five days after full bloom (DAFB) and carbaryl at 15 DAFB. The volume did not play a major role on the efficiency of the treatments on fruit thinning: the different spray volumes showed similar thinning efficiency on 'Gala' apple. Except at 430 L/ha, chemical thinners sprayed at different volumes gave fruit weight and percentage of fruits ≥66 mm greater than the control, but did not differ among them.